ANALISIS MANFAAT PINJAMAN PT. PEGADAIAN TERHADAP OMSET PEDAGANG SAYUR DI KABUPATEN SAMBAS - B01107075, RODI (Jurnal Pembangunan dan Pemerataan, 2015)
This study entitled "Analysis ofLoanBenefitsPT. PawnAgainstAgainstturnoverVegetableMerchantsSambasregency". The problem in this research is how the "Impact Sambas Pawnshop loans to increase business development for small traders Sambas", while the purpose of this study to determine the impact of the credit given to the improvement of business development for small traders in the district Sambas. This research used descriptive method, a method that describes the circumstances that actually occurred. Retrieval of data by using the kueosioner, interviews and observations. Sampling technique with a simple random sample of the total respondents 10% or 15 respondents as a small trader by profession pawnshop customers. The results of the study most of the respondents felt the real impact of the loans granted by the pawnshop, the visible impact of increased income business, assets increased efforts to make their business volume has increased so that the operating profit increased. Keywords: benefits, Credit, Improvement, turnover, efforts